2001
DOI: 10.3189/172756401781819634
|View full text |Cite
|
Sign up to set email alerts
|

On the characterization of seismic signals generated by snow avalanches for monitoring purposes

Abstract: Seismic signals from artificially released avalanches were studied in an attempt to characterize them for avalanche-monitoring purposes. The seismic signals generated by different sizes and types of avalanches were recorded and analyzed in the time and frequency domains. Synchronized recordings of the corresponding seismic signals and the video images of the evolution of the avalanches were obtained together with a detailed cartography. Characteristic signatures in the frequency and time domains were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 5 publications
0
55
0
Order By: Relevance
“…If three‐component seismic data are available within a short distance from the source, calculations of the total received energy might be more representative than only horizontally polarized signals. However, many stations still record only vertical components, and Suriñach et al [2001] have shown that the absolute amplitudes in three‐component signals can be different, while seismic energy and frequency content are similarly distributed. Because our analysis is based only on the shape of the seismograms (amplitude envelopes, Figures 3 and 5) and not on the magnitudes, the vertical component should sufficiently well represent the information needed for comparison with modeling results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If three‐component seismic data are available within a short distance from the source, calculations of the total received energy might be more representative than only horizontally polarized signals. However, many stations still record only vertical components, and Suriñach et al [2001] have shown that the absolute amplitudes in three‐component signals can be different, while seismic energy and frequency content are similarly distributed. Because our analysis is based only on the shape of the seismograms (amplitude envelopes, Figures 3 and 5) and not on the magnitudes, the vertical component should sufficiently well represent the information needed for comparison with modeling results.…”
Section: Discussionmentioning
confidence: 99%
“…Seismic source signal: This is the seismic signal produced by the avalanche directly at the site of the event. The strength of the produced signal is related to the total momentum, respectively total kinetic energy of the avalanche (which in turn depend on mass and velocity, and hence also on entrainment [ Suriñach et al , 2001, 2005]). Furthermore, the production of seismic energy is affected by the surface properties of the avalanche path which include surface roughness (on a millimeter to decameter scale), but also centrifugal and impact effects caused by minor and major obstacles, topographic steps and lateral deflections [ McSaveney and Downes , 2002; Sabot et al , 1998; Suriñach et al , 2001].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…and of its dynamics and mechanical behaviour (velocity, friction coefficient, etc.) [ Suriñach et al , 2001; Brodsky et al , 2003; La Rocca et al , 2004; Vilajosana et al , 2007; Huggel et al , 2007; Deparis et al , 2008; Cole et al , 2009].…”
Section: Introductionmentioning
confidence: 99%